The Argentine Continental Margin: A Potential Paleoclimatic-Paleoceanographic Archive for the Southern Ocean - Violante, Roberto Antonio; Laprida, Cecilia; García Chapori, Natalia Luz
The Argentina Continental Margin, located in the Southwestern Atlantic Ocean, is inserted in a key region of the World Ocean due to its significance in the global oceanographic-climatic interaction, and because it is the only place where Antarctic- and Equator-sourced water-masses interact in mid-latitudes. On the other hand, the geotectonic history of the region imprints it with significant geological characteristics. As a result, the climatically-, oceanographically- and physically-driven sedimentary processes occurred in the region originated particular and almost unique morphosedimentary features, which constitute complete records of the processes involved in its evolution. Those features contain different kinds of proxies, tracers and records (biological, geochemical, sedimentological, morphological and structural) which provide valuable quantitative and qualitative evidences for detailed paleoceanographic, paleoclimatic and paleoenvironmental reconstructions. Therefore, the Argentine margin potentially behaves as a complete archive for understanding most of the unique oceanographic and climatic characteristics that occur in the region and impact in the rest of the Southern Hemisphere. Fil: Violante, Roberto Antonio. No especifíca; Fil: Laprida, Cecilia. Consejo Nacional de Investigaciones Científicas y Técnicas. Oficina de Coordinación Administrativa Ciudad Universitaria. Instituto de Estudios Andinos "Don Pablo Groeber". Universidad de Buenos Aires. Facultad de Ciencias Exactas y Naturales. Instituto de Estudios Andinos "Don Pablo Groeber"; Argentina Fil: García Chapori, Natalia Luz. Consejo Nacional de Investigaciones Científicas y Técnicas. Oficina de Coordinación Administrativa Ciudad Universitaria. Instituto de Estudios Andinos "Don Pablo Groeber". Universidad de Buenos Aires. Facultad de Ciencias Exactas y Naturales. Instituto de Estudios Andinos "Don Pablo Groeber"; Argentina